Simple estimation methods for noise reduction by variously shaped barriers - MAEKAWA, Z. (Archives of Acoustics, 1985)
Simple estimation methods for various noise barriers are reviewed from the practical point of view of noise control. Some simple charts for the barriers of various bodies are found by experimental and theoretical studies. It has been clear that the integral equation method is useful to predict the noise reduction by a semi-transparent barrier.